2015
DOI: 10.1039/c5tc00662g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface topography on the field emission of nanostructured copper oxide thin films grown by oblique incidence deposition

Abstract: We report the surface morphology dependent enhanced field electron emission properties of copper oxide thin films, which are sputter deposited at two different incidence angles. The turn-on field is as low as 1.3 V µm -1 for obliquely deposited thin film, with an enhancement factor of ~ 5144. The emission current also shows good stability. With the help of finite element method analysis, we show that the enhanced field emission behaviour is due to the special surface topography of obliquely deposited film. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…It is well known that carrier density available for electrical transport in a material strongly depends on its crystallinity . Thus, XRD spectra are recorded under similar conditions to further confirm the crystalline nature of Cu 2 O films deposited on flat ‐ and text ‐Si substrates.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It is well known that carrier density available for electrical transport in a material strongly depends on its crystallinity . Thus, XRD spectra are recorded under similar conditions to further confirm the crystalline nature of Cu 2 O films deposited on flat ‐ and text ‐Si substrates.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, it should be noted that R plays an important role in determining the internal quantum efficiency (IQE), since IQE = EQE/(1‐ R ), where EQE is the external quantum efficiency . It also needs a mention that the efficiency also depends on the electrical transport properties of the studied solar cell …”
Section: Resultsmentioning
confidence: 99%
“…Mostly different nano‐ composite materials like rGO‐ Ag nanoparticle, Ag–AgCl/ZnFe 2 O 4 magnetic nanocomposite, Ag@helical chiral TiO 2 nanofibers has been used for the degradation of different endrocrine disruptors. However our aim was to use a single component as photocatalyst as recent research shows fascinating results with respect to synthesis, band gap tuning, field electron emission,, thermal energy conversion, energy storage,, catalyst,, hydrophobic surfaces,, gas adsorbant etc. Some specific examples of photocatalytic removal of E1 and EE2 are given in Table .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that following implantation the film remains granular in nature, albeit the RMS roughness as well as the average grain size increases with fluence (see Figure D). Besides film morphology, the nature of the crystallinity also plays an important role in determining the electrical properties of a thin film , and hence, XRD measurements of as-grown and implanted TiO x films are carried out (Figure E) which reveal their amorphous nature. In addition, the influence of implantation on the optical and electrical properties of TiO x layers are studied.…”
Section: Resultsmentioning
confidence: 99%